2011
DOI: 10.1002/app.33843
|View full text |Cite
|
Sign up to set email alerts
|

A new Schiff base epoxy oligomer resin: Synthesis, characterization, and thermal decomposition kinetics

Abstract: Oligo{2,2 0 -{1,4-phenylenebis[nitrilomethylylidene]}bis(6-methoxyphenol)} (OPNMMP) was synthesized from o-vanillin and p-phenylene diamine by oxidative polycondensation with NaOCl in an aqueous alkaline. Then, a new Schiff Base epoxy oligomer resin, OPNMMP-epichlorohydrine (EPC), was produced with EPC. The structures of the resulting compounds were confirmed by Fourier transform infrared spectroscopy, ultraviolet-visible spectroscopy, 1 H-NMR, and 13 C-NMR. Further characterization processes were preformed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Some research teams have already reported works on vanillin for epoxy synthesis and various applications. A Schiff base synthesized was used for metal ion chelation applications (Scheme ) …”
Section: Biobased Building Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research teams have already reported works on vanillin for epoxy synthesis and various applications. A Schiff base synthesized was used for metal ion chelation applications (Scheme ) …”
Section: Biobased Building Blocksmentioning
confidence: 99%
“…A Schiff base synthesized was used for metal ion chelation applications (Scheme 27). 133 Moreover, vanillin was used to synthesize biobased epoxy monomer by a chemoenzymatic process with Candida antartica lipase 134 (Scheme 28). In all cases, epoxy networks exhibited interesting thermal properties.…”
Section: Biobased Building Blocksmentioning
confidence: 99%
“…6,7 Because of the above-mentioned limitations associated with the use of bulk lignin, use of well characterized lignin-derived monomers for thermosets design is most appealing and has received extensive attention. Thermosets including epoxy resins, polybenzoxazines, vinyl ester resins and cyanate ester resins developed from lignin-derived building blocks like eugenol, 8,9 vanillin, 10,11 guaiacol 12 and creosol 13 have been reported. Improved reactivity of lignin-derived monomers rather than bulk lignin provides thermosets that exhibit more satisfactory mechanical and thermal properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…According to Kissinger's method and using Equation ( 8), the activation energy can be estimated by plotting Ln(β/ T p 2 ) versus 1/T p and fitting a straight line to the data points. [100,101] Slope of lines show E/R values. Calculation of activation energy through this method is shown in Figure S5.…”
Section: Thermal Stability Analysis Of Samplesmentioning
confidence: 99%